Dissemination and Reterritorialization - Kuan-min Huang (Asian Studies, 2020)
Confucianism as a mode of life was brought to Taiwan as early as Chinese settlement. Regarding Confucian philosophy, however, it must be traced back to the founding of modern institutions. Even though the historical background of the Chinese diaspora after 1949 is rather complex, it seems possible to examine how it has contributed to the development of academic disciplines in Taiwan, especially with regard to Confucianism. The present paper investigates the corresponding contributions of two philosophers, Tang Junyi (1909–1978) and Mou Zongsan (1909–1995). Both are important scholars, who are indispensable for the development of contemporary intellectual history in Taiwan. In order to describe the creativity in their way of dealing with ruptures, of transforming the separation into the renovation of tradition, the author analyses their efforts in terms of geo-philosophy, through the lens of two concepts, dissemination and reterritorialization, that are borrowed from Jacques Derrida, Gilles Deleuze, and Felix Guattari.